2020
DOI: 10.3390/ma13163621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reclaimed Asphalt Pavement Heating Temperature on the Compactability of Recycled Hot Mix Asphalt

Abstract: The compactability of an asphalt mixture is related to the heating temperature of the materials, but the heating temperature of reclaimed asphalt pavement (RAP) is limited by the production process of hot-in-plant recycled mixtures. To choose a reasonable heating temperature for RAP according to the compactability, the compaction energy ratio (CER) obtained from the Superpave gyratory compactor compaction curve was developed. The CERs of fourteen kinds of asphalt mixtures made with different RAPs were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…The test were conducted on the mechanical properties of AC-20 ordinary asphalt recycled mix and AC-13 modified asphalt recycled mix with different blending ratios (0, 20, 40, and 50%, respectively) in which 5% of the same recycler is added to both recycled materials with 40% RAP blending for performance comparison. The heating temperature of RAP is 120 °C for the best compaction characteristics of the mix (Ma et al, 2020), and the test at this temperature has a molding diameter of 150 mm, height of 150 mm rotary compaction specimens and the number of compaction for 100 times, dynamic modulus test; the test process is shown in Figures 1A-C. Loading frequencies of 0.1, 0.5, 1, 5, 10, and 25 Hz were used for repeated loading tests under temperature conditions of -10 °C, 5 °C, 20 °C, 35 °C, and 50 °C, respectively, and the temperature was carried out from low to high temperatures, in turn, whereas the frequency was carried out from high to low frequency, in turn; the load and deformation curves of the last five waveforms were collected for the test, and the average of the three was taken for each specimen type as the final result.…”
Section: Dynamic Modulus Testmentioning
confidence: 99%
“…The test were conducted on the mechanical properties of AC-20 ordinary asphalt recycled mix and AC-13 modified asphalt recycled mix with different blending ratios (0, 20, 40, and 50%, respectively) in which 5% of the same recycler is added to both recycled materials with 40% RAP blending for performance comparison. The heating temperature of RAP is 120 °C for the best compaction characteristics of the mix (Ma et al, 2020), and the test at this temperature has a molding diameter of 150 mm, height of 150 mm rotary compaction specimens and the number of compaction for 100 times, dynamic modulus test; the test process is shown in Figures 1A-C. Loading frequencies of 0.1, 0.5, 1, 5, 10, and 25 Hz were used for repeated loading tests under temperature conditions of -10 °C, 5 °C, 20 °C, 35 °C, and 50 °C, respectively, and the temperature was carried out from low to high temperatures, in turn, whereas the frequency was carried out from high to low frequency, in turn; the load and deformation curves of the last five waveforms were collected for the test, and the average of the three was taken for each specimen type as the final result.…”
Section: Dynamic Modulus Testmentioning
confidence: 99%
“…However, the mechanisms of the thermal production conditions and their influences on the performance of RAP mixtures are not well understood [42]. For example, Ma et al [43] found out that increasing the heating temperature of RAP is not always an effective method to improve the compactability of recycled HMA. The recycled HMA mixtures containing 20% RAP are easier to compact with RAP heated to 120 • C than the same mixtures with RAP heated to 140 • C. Sivilevičius and Vislavičius [44] proposed algorithms that were developed by using mathematical programming methods, which helped to minimise the bitumen content and, as a result, reduced the final product price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, many scholars prepare asphalt mixture from regenerated SBS-modified asphalt and then evaluate the rejuvenation effect by testing the technical performance of the mixture [22][23][24][25]. ese performances include rutting resistance and fatigue cracking performance [26,27], stress creep recovery [28], compaction performance [29], durability [30], and viscoelasticity [31].…”
Section: Introductionmentioning
confidence: 99%